2019
DOI: 10.5194/hess-23-1905-2019
|View full text |Cite
|
Sign up to set email alerts
|

Identifying El Niño–Southern Oscillation influences on rainfall with classification models: implications for water resource management of Sri Lanka

Abstract: Abstract. Seasonal to annual forecasts of precipitation patterns are very important for water infrastructure management. In particular, such forecasts can be used to inform decisions about the operation of multipurpose reservoir systems in the face of changing climate conditions. Success in making useful forecasts is often achieved by considering climate teleconnections such as the El Niño–Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) as related to sea surface temperature variations. We present a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Seasonal analysis showed increase in rainfall during FIM, SIM and NEM, but there is decrease in rainfall during SWM. SWM rain brings more rainfall to wet zone (De Silva and Hornberger, ) and it is the source of water of main perennial rivers in Sri Lanka and it contribute in hydro power generation and irrigating larger area of dry zone Sri Lanka. Thus decrease in rainfall during SWM period likely to affect the economy of the country.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seasonal analysis showed increase in rainfall during FIM, SIM and NEM, but there is decrease in rainfall during SWM. SWM rain brings more rainfall to wet zone (De Silva and Hornberger, ) and it is the source of water of main perennial rivers in Sri Lanka and it contribute in hydro power generation and irrigating larger area of dry zone Sri Lanka. Thus decrease in rainfall during SWM period likely to affect the economy of the country.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic climate teleconnections such as El Niño‐Southern Oscillation (ENSO), Indian Ocean Dipole (IOD) and Quasi‐Biennial Oscillation may also influence these trends. It is reported that during El Niño event rainfall increases for the first three months of the Maha season (October–December), and decreases during the last three months (January–March) (Ropelewski and Halpert, ; De Silva and Hornberger, ). Similarly, La Niña events enhance the rainfall during the SWM (Whitaker et al ., ; De Silva and Hornberger, ), whereas during El Niño events the SWM rainfall is reduced (Chandimala and Zubair, ; De Silva and Hornberger, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quadratic discriminate function is derived by taking the logarithmic values, as given in (7). For class k(π k ), prior probabilities are calculated by taking the frequency of data points of class k in the training data, as in (8). If we consider N number of points totally in the training observations, then N k represents the number of observations corresponding to the k th class.…”
Section: A Quadratic Discriminate Analysis (Qda)mentioning
confidence: 99%
“…Studies made by Yadav et al [7] found that the inter annual variability of North West India Winter Precipitation is influenced by Arctic Oscillation / North Atlantic Oscillation (AO/NAO) and El Nino -Southern Oscillation (ENSO) phenomena. T. De Silva M et al [8] have made an attempt to forecast the rainfall of Mahaweli and Kelani River basins of Sri Lanka. Cao et al [9] investigated the rainy-season precipitation in China based on the influence of five El Nino-Southern Oscillations indices.…”
Section: Introductionmentioning
confidence: 99%